2016
DOI: 10.1002/anie.201608536
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Electrokinetic Phenomena: Setting the Record Straight

Abstract: Electro-osmosis and electrophoresis were discovered by F. F. Reuss in Moscow in 1807. Or so the story goes. This Essay critically examines the contributions of three scientists to the discovery of electrokinetic phenomena. The evidence suggests that Reuss did indeed discover electro-osmosis, which takes its name (indirectly) from the work of Porrett. Contrary to current consensus, Gautherot made the earliest known observation of electrophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…He stated that the liquid between the poles of a battery is continuously driven from the positive pole toward the negative pole. He also believed that the presence of porous barriers makes this movement visible by counteracting the impact of gravity [28]. While some previous works supported his conclusions [31,32], later in this article we will show that according to our modern understanding, these conclusions are false.…”
Section: History and Backgroundmentioning
confidence: 59%
See 2 more Smart Citations
“…He stated that the liquid between the poles of a battery is continuously driven from the positive pole toward the negative pole. He also believed that the presence of porous barriers makes this movement visible by counteracting the impact of gravity [28]. While some previous works supported his conclusions [31,32], later in this article we will show that according to our modern understanding, these conclusions are false.…”
Section: History and Backgroundmentioning
confidence: 59%
“…While some previous works supported his conclusions [31,32], later in this article we will show that according to our modern understanding, these conclusions are false. Biscombe [28] has reviewed the history of EOF discovery, which can be referred for further details.…”
Section: History and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Water molecules diffuse through the solute from the solvent layer. 142 Bruhn et al demonstrated the development of devices that are capable of pressure generation based on the osmosis principle, which could be made from available low-cost materials. 143 Some MFD and LOC devices using osmosis as a passive approach for their operation are shown in Fig.…”
Section: Osmosismentioning
confidence: 99%
“…Though this electrokinetic phenomenon was first observed by French chemist Nicolas Gautherot back in the early nineteenth century, Herbert Pohl first coined the term “dielectrophoresis” in 1951 and demonstrated and explained characteristics of DEP in particle trapping [17–19]. Over the last decade, a wide variety of DEP‐based microfluidic devices have been developed for the separation of synthetic particles, for example, polystyrene beads, and bioparticles, for example, cell, bacteria, and proteins.…”
Section: Introductionmentioning
confidence: 99%